Pengaruh Pengungkapan Emisi Karbon terhadap Risiko Keuangan Perusahaan Minyak dan Gas Global: Systematic Literature Review - Ramadhan, M. Faalih Athoullah; Al Ghazali, Muhammad; Asyifa, Adinda Putri; Putri, Salwa Nabilah; Kirana DP, Rina Tjandra (GLOBAL SCIENTS PUBLISHER, 2026)
The global energy transition forces the oil and gas industry to adopt carbon emission disclosures, yet its impact on financial risk remains highly polarized. This study aims to synthesize the effect of carbon emission disclosure on financial risk metrics in global oil and gas companies. Utilizing a Hybrid Systematic Literature Review (SLR) approach, this research integrates bibliometric analysis and thematic synthesis of 25 selected articles (2020-2026) sourced from Google Scholar. The findings reveal a sharp empirical polarization. A total of 15 articles confirm that carbon disclosure acts as a positive signal, effectively reducing information asymmetry and mitigating financial risks. Conversely, 10 articles demonstrate valuation anomalies where climate transparency escalates financial vulnerability due to anticipated surges in operational costs, asset impairment threats, and indications of greenwashing practices aimed solely at maintaining social legitimacy. In conclusion, the effectiveness of carbon disclosure as a financial risk mitigator heavily relies on data credibility and corporate governance quality.